Role of Bullock Carts and Trucks in Rural Transport - Case Studies - Planning Commission (Planning Commission, 1963)
At the instance, and on behalf of the Committee on Transport policy and Coordination, appointed by the Planning Commission, the Programme Evaluation Organisation undertook to study the role played by bullock carts and other traditional modes of transport in rural areas. This happens to be one of the fields in which very few studies have so far been conducted, and on which the available information is sadly inadequate. In fact, there is practically nothing that will throw light on the changes, if any. that have taken place in the role of these traditional means of rural transport. Under these circumstances, it was decided to make this study more or less of an exploratory nature, conducted with the help of the case method. An estimational survey was accordingly ruled out.
Undertaken at the Instance of Committee on Transport Policy and Coordination